2019
DOI: 10.1007/s10936-019-09661-y
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Concepts Related to Love Spectrum: Emotional Verbal Fluency Technique Application, Initial Psychometrics, and Its Validation

Abstract: Love has been thoroughly studied and a variety of definitions as well as types of love have been described in the literature. Given the data presenting natural language of love concept, the aim of the two present studies is to demonstrate a new technique which enables description of the structure of emotion concepts within love spectrum. This technique is based on emotional verbal fluency tasks. The procedure and the coding system used are reported in the article along with the data on reliability and standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The subject of this study directly correlates and continues to develop the problems of structuring individual concepts and their contrastive comparison, cross-cultural lexicography, emotional semantics, etc. (Bahn, Kauschke, Vesker & Schwaryer, 2018;Gawda, 2019;Kulpina & Tatarinov, 2018;Lomas, 2016;Du, Tao & Martinez, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The subject of this study directly correlates and continues to develop the problems of structuring individual concepts and their contrastive comparison, cross-cultural lexicography, emotional semantics, etc. (Bahn, Kauschke, Vesker & Schwaryer, 2018;Gawda, 2019;Kulpina & Tatarinov, 2018;Lomas, 2016;Du, Tao & Martinez, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Words given by the subject are semantically connected and form semantic clusters. A semantic network composed of semantic clusters reflects the structure of the emotional concept (Gawda, 2019). Previous research (Gawda, 2019) showed that the EVFT is a reliable and valid technique.…”
Section: Methods and Participantsmentioning
confidence: 99%
“…A semantic network composed of semantic clusters reflects the structure of the emotional concept (Gawda, 2019). Previous research (Gawda, 2019) showed that the EVFT is a reliable and valid technique. Inter-judge reliability of the tool is very good (ranging from 0.87 to 0.99) and test-retest correlation is high (ranging from 0.76 to 0.92).…”
Section: Methods and Participantsmentioning
confidence: 99%
“…Verbal fluency techniques are among the well-known and widely recognized psychological tools used in assessing cognitive functions (Ardila and Ostrosky-Solís 2006). These techniques require a spontaneous word generation from predefined categories (Gawda andSzepietowska 2013, 2016). The standard applications of verbal fluency techniques relate to letter and category fluency tasks and quantitative analysis.…”
Section: Emotional Verbal Fluencymentioning
confidence: 99%